Selective synthesis of methanol by photoelectrocatalytic reduction of CO2 over PANI-CuFe2O4 hybrid catalyst. Issue 4 (January 2020) - Rezaul Karim, K M; Tarek, M; Sarkar, S M; Ong, H R; Abdullah, H; Cheng, C K; Rahman Khan, M M
Abstract: In this work, a hybrid photocatalyst, PANI-CuFe2 O4 was synthesized, characterized and used as a photocathode for the photoelectrocatalytic (PEC) reduction of CO2 to methanol selectively under 470 nm wavelength light irradiation at applied potential -0.4 V vs NHE. The PEC results showed that the combination of PANI with CuFe2 O4 could increase the rate of PEC CO2 reduction to methanol owing to the increase of CO2 chemisorption at the photocathode surface and at the same time by facilitating the separation of photogenerated electron-hole (e − /h + ) pairs during CO2 reduction. The rate of methanol formation was found maximum as 49.2 μmole g −1 .h −1 with 73% Faradaic efficiency. The incident photon current efficiency (IPCE) and quantum efficiency (QE) for PEC CO2 reduction was achieved as 7.11% and 23.9% respectively. The PEC results demonstrated that the bias potential played a significant role in the separation of e − /h + pairs and enhanced the PEC CO2 reduction activity of the hybrid photocatalyst.